Sumerian Letters: Two Collections from the Old Babylonian Schools - Ali, Fadhil Abdulwahid (1964)
Ph. D. dissertation; Supervisor: S. N. Kramer. University Microfilms, Inc., 313 North First Street, Ann Arbor, Mich. Order No. 64-10,343 (Microfilm $2.80, Xerograph $9.70). Abstracts: Dissertation Abstracts 25/7 (Ann Arbor, Mich., January 1965) 4131. Linguistics 18 (The Hague 1965) 84.